Enamine‐Based Cross‐Linkable Hole‐Transporting Materials for Perovskite Solar Cells. Issue 1 (7th January 2021) - Vaitukaitytė, Deimantė; Al-Ashouri, Amran; Daškevičienė, Marytė; Kamarauskas, Egidijus; Nekrasovas, Jonas; Jankauskas, Vygintas; Magomedov, Artiom; Albrecht, Steve; Getautis, Vytautas
Abstract : Perovskite Solar Cells Solution‐processing of the photoactive layer on top of the hole‐transporting material can be challenging.Solvent damage leads to the formation of direct contact with the electrode, and consequently to reduced performance parameters. In article number 2000597, Vytautas Getautis and co‐workers show that cross‐linking of the organic semiconductor is advantageous for application in the p‐i‐n perovskite solar cells.